PENERAPAN SISTEM INFORMASI MANAJEMEN PEMASARAN DALAM MENINGKATKAN OMZET UMKM KULINER MAKANAN KOTA MAKASSAR - Rustan Unismuh; Andi Arifwangsa Adiningrat; Siti Aisyah; Andi Rustam; Warda .; Rendra Anggoro (Universitas Muhammadiyah Luwuk Banggai, 2022)
This study aims to determine the application of marketing management information systems in increasing the turnover of Micro, Small and Medium Enterprises (MSMEs). The time and place of this research was carried out for two months in several 7 Food Culinary SMEs in Makassar City. Data collection techniques were carried out by means of library research, interviews and field observations. The analytical method used in this research is multiple linear regression analysis. Linear regression analysis method The analytical method that will be used by the author is an applied qualitative descriptive method. The data analysis was carried out using qualitative data analysis. There are several subsystems in increasing the turnover of MSMEs through marketing outputs, namely the product subsystem, the price subsystem, the place subsystem, the promotion subsystem and the marketing mix. Marketing information systems have several functions in a business, namely assessing information needs, developing needed information, and distributing information